Penguatan Self-Efficacy dan Dukungan Sosial Keluarga untuk Menurunkan Risiko Stunting pada Balita - Jefania Valda; Rostika Flora; Suci Destriatania (Jurnal Medika: Medika, 2025)
Stunting is one of the most crucial public health problems in low- and middle-income countries, including Indonesia, as it reflects chronic growth failure due to the interaction of nutritional factors, infections, and inadequate parenting practices. Although nutritional interventions have been widely implemented, psychosocial determinants such as self-efficacy and maternal social support have received less attention, even though both play an important role in parenting practices during the 1000 HPK period. This activity was carried out using an evidence-based approach, namely developing an educational and assistance package for stunting prevention that emphasizes strengthening the self-efficacy of parents/caregivers and social support from families and communities. The synthesis results show that self-efficacy contributes to adaptive parenting practices, including feeding, hygiene, and seeking health services, while social support plays a role in improving emotional stability, coping, and maternal parenting capacity. The findings also indicate a synergistic interaction between these two determinants in reducing the risk of stunting. Therefore, the results of this study emphasize that stunting prevention strategies need to integrate a psychosocial approach through increasing self-efficacy and strengthening social support to achieve more comprehensive and sustainable intervention effectiveness.